CFC fluids and their harmful influence - Ciconkov, Risto (Macedonian Journal of Ecology and Environment, 1995)
Refrigerants in the first vapor compression refrigeration systems and progressive evolution. An appearance of CFC refrigerants and enlargen expanding its use in refrigeration systems and other applications. First informations about the harmful influence of the CFC fluids on the ozone layer and the "greenhouse effect". International associations activities for reduction and phase out of CFCs and HCFCs.